Graphene and Copper Constituted Hybrid Metasurface Enhanced Terahertz Sensing for Biomedical Applications - Sahu D.; Panwar E.; Panwar R. (My University, 2025)
This letter presents the design, analysis, and application of a versatile metasurface (MS) absorber in the terahertz (THz) frequency range. Initially, a microwave multiband MS absorber is conceived, fabricated, and characterized within the 2-18 GHz range, exhibiting remarkable absorption properties with six distinct peaks exceeding 98%. Subsequently, the letter explores the innovative application of a copper-based MS absorber at THz frequencies. This absorber demonstrates exceptional performance attributes, including 99% absorptivity at 3.48 THz with a narrow absorption bandwidth of 0.087 THz, all achieved within an ultrathin profile of 2.4 μm. Moreover, the copper-based MS-inspired absorber serves as the foundation for the development of a THz biosensor, particularly for glucose-sensing applications. This biosensor exhibits sensitivity to the refractive index (RI) of the surrounding medium, enhancing analytical capabilities at a constant analyte thickness of 6.0 μm. To further augment sensing performance, a new kind of hybrid sensor design, i.e., integrating graphene and copper, is investigated for glucose, malaria, and cancer cell detection. The results underscore the vast potential of the proposed MS configuration for a wide spectrum of THz sensing applications, including medical diagnostics and disease detection, harnessing the power of MS to bridge the gap between electromagnetics and biosensing realms. © 2017 IEEE.